Saccadic delay in multiple sclerosis: A quantitative description. (March 2020) - Nij Bijvank, J.A.; Petzold, A.; Coric, D.; Tan, H.S.; Uitdehaag, B.M.J.; Balk, L.J.; van Rijn, L.J.
Abstract: In multiple sclerosis (MS), eye movement disorders are common and can be quantified with infrared video-oculography. A well-known abnormality is internuclear ophthalmoplegia (INO). This study aims to describe saccadic abnormalities beyond INO and investigate their clinical relevance. A validated standardized infrared oculography protocol, DEMoNS, was used for quantifying saccadic eye movements in three different tasks in MS patients and healthy controls. The relationship between the saccadic parameters and disease characteristics was investigated. Furthermore, the association between saccadic parameters and visual functioning was analysed using logistic regression models, adjusted for possible confounders. This cross-sectional study included 218 subjects with MS and 58 healthy controls. The latency of all saccades was longer in MS patients than in healthy controls. This saccadic delay was larger in subjects with a longer disease duration and more disabled subjects. Furthermore, it was significantly related to presence of a lower vision-related quality of life. This study provided a comprehensive overview of performance of MS patients in different saccadic tasks, compared to healthy controls. Saccadic delay in MS patients was present in all saccadic tasks and was related to advancing disease and visual functioning in daily life.